Al-Azdawī on the early qiblah orientation based on thematic analysis of al-Hadīth and astrometry - Ahmad Irfan, Ikmal Hisham; Ishak, Suliaman; Radiah, Abdul Ghani; Norazmi, Anas; Zakiah, Samori (Hamdard Foundation, 2020)
After the expansion reached Transoxania- a classical name of Central Asia, al- Bazdawī realized a significant distortion of Qiblah azimuth, hence a need to revise the orientation procedure, based on contextual understanding of al-Ḥadīth. Consequently, al- Bazdawī wrote a treatise to inform that the later Ḥanafīs took the Qiblah in Transoxania as due west, and that the Shāfi„īs took it as due south. This study has employed thematic analysis on al-Ḥadīth used in all the arguments, which were understood mainly by early scholars, textually, without considering it contextually, based on the astronomical aspects. This includes the study of asbāb wurūd al-ḥadīth, authenticity, reviewing al-Bazdawī‟s treatise and mathematical analysis. The outcome of the study suggests that the application of topical ḥadīth on qiblah must critically be applied based on scientific and astronomical calculation. In conclusion, ḥadīth is one of the scientific miracles of the prophet Muhammad that must be applied within its context. Simple application based on textual understanding can lead towards the significant error in „ibādah, both technically and fundamentally.